Influencia de las Imágenes en la creación de Cuentos Infantiles por los estudiantes del cuarto grado de Educación Primaria de la Institución Educativa N° 81007 Modelo - Trujiillo, 2016 - Rojas Gavidia, Angelica Maria (2017)
The present investigation was carried out with the objective of determining the influence of the use of images in the creation of children’s stories in the 4th grade students of the I.E 81007 "Modelo", of the city of Trujillo in the year 2016._x000D_ The population was 150 students and the sample was 25 students as an experimental group and 25 students as a control group to whom the measurement instruments were applied._x000D_ The research for its purpose was applied type, with a quasi experimental design, information collection and processing techniques were used and as instrument a test was applied that was validated by expert judgment and determined its reliability based on a pilot test._x000D_ The results that were reached were that students of the experimental group after having applied the sessions of use of images for the creation of stories managed to improve significantly as evidenced by the difference between the pretest and post test whose score was 2, 6 equivalent to 8.6%. While the students of the control group according to the comparative tables of the pretest and pos test on the use of images for the creation of stories did not achieve a minimum increase as demonstrated by the difference of 0.2 equals 1,4 %._x000D_ Based on these results, the hypothesis test was performed using Student's t-test, confirming the hypothesis of the present investigation and rejecting the null hypothesis._x000D_ Therefore, it was concluded that the use of images influences significantly the improvement of the creation of children's stories, in the 4th grade students of the I.E. N ° 81007 "Model" of Trujillo - 2016.